2018
DOI: 10.1371/journal.pntd.0006448
|View full text |Cite
|
Sign up to set email alerts
|

Development of a single-tube one-step RT-LAMP assay to detect the Chikungunya virus genome

Abstract: BackgroundA single-tube one-step real-time reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for rapid detection of chikungunya virus (CHIKV) targeting the conserved 6K-E1 target region was developed. The assay was validated with sera collected from a CHIKV outbreak in Senegal in 2015.Methodology/Principal findingsA novel design approach by combining Principal Component Analysis and phylogenetic analysis of 110 available CHIKV sequences and the LAMP oligonucleotide design software LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…More recently, related studies have been reported (Lopez-Jimena et al, 2018 andHayashida et al, 2019). Thus, we compared the sensitivity and specificity of our RT-LAMP system to those of their systems.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, related studies have been reported (Lopez-Jimena et al, 2018 andHayashida et al, 2019). Thus, we compared the sensitivity and specificity of our RT-LAMP system to those of their systems.…”
Section: Discussionmentioning
confidence: 99%
“…Some highlights from adaptations of LAMP include multiplexed LAMP, electrochemical LAMP, and disc-based LAMP [46][47][48]. For RNA viruses, such as ZIKV, DENV, and CHIKV, it is necessary to perform a reverse transcription reaction LAMP (RT-LAMP) [27,39,42,[49][50][51][52] which includes the enzymes that first convert RNA → DNA upstream of the LAMP process, unless a LAMP enzyme with both reverse transcriptase and DNA polymerase is used [53].…”
Section: Principles Of Lamp Assaymentioning
confidence: 99%
“…Other molecular methods for detecting pathogenic viruses such as direct nucleic acid detection by a biosensor (Saylan et al, 2019) and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) diagnostics using CRISPR-CRISPR-associated system (CRISPR-Cas) (Chertow, 2018) have also been developed. In addition, loop-mediated isothermal amplification (LAMP), a recent development of a diagnostic method offers advantages in terms of sensitivity, specificity, efficiency and rapidity and can be performed at the point of care for detection of emerging viruses (Notomi et al, 2000;Wong et al, 2017;Lopez-Jimena et al, 2018;Sabalza et al, 2018).…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%